Pelatihan Penerapan Rekonsiliasi dan Kesatuan dalam Roma: Berbasis Tologi PL-PB untuk Membangun Gereja Oikumene dan Khotbah Transformatif - Salomi Dina Djami; Damianus Moruk; Benny Leons Gilon; Eben Hezer Plaimo (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2026)
The Community Service Activity of the Indonesian Evangelical Theological College (STTII) Kupang at the Indonesian Bethel Church (GBI) Shekinah Glory-Namosain Kupang explored the theme "Training on the Application of Reconciliation and Unity in Romans: Based on OT-NT Theology to Build an Ecumenical Church and Transformative Sermons" which aims to overcome divisions within the church through a theological approach based on the Old Testament (OT) and New Testament (NT), especially the letter to the Romans. The background of this activity is based on the reality of church denominational divisions that hinder the mission of evangelization and the building of a harmonious society, so that training is needed to promote reconciliation and unity as the foundation of the ecumenical church. The methods used include interactive workshops, group discussions, and transformative sermon simulations, which involve participants in the local church community. The results of the activity show an increase in participants' understanding of the theology of reconciliation in Romans, with indicators such as the ability to design sermons that encourage social and spiritual change. The conclusion of this activity is that this training has succeeded in building ecumenical awareness, strengthening solidarity, and providing long-term benefits to the community through more inclusive and transformative preaching, thus contributing to the building of a more peaceful and united society.